Imaging of single-molecule translocation through nuclear pore complexes - Yang, Weidong (National Academy of Sciences, 2004)
Nuclear pore complexes (NPCs) mediate bidirectional transport of proteins, RNAs, and ribonucleoprotein complexes across the double-membrane nuclear envelope. In vitro studies with purified transport cofactors have revealed a general scheme of cofactor-dependent transport energetically driven by the G protein Ran. However, the size and complexity of NPCs have made it difficult to clearly define the loci and kinetics of the cofactor–NPC interactions required for transport. We now report the use of single-molecule fluorescence microscopy to directly monitor a model protein substrate undergoing transport through NPCs in permeabilized cells. This substrate, NLS-2xGFP, interacts with NPCs for an average of 10 ± 1 ms during transport. However, because the maximum nuclear accumulation rate of NLS-2xGFP was measured to be at least ≈10(3) molecules per NPC per s, NPCs must be capable of transporting at least ≈10 substrate molecules simultaneously. Molecular tracking reveals that substrate molecules spend most of their transit time randomly moving in the central pore of the NPC and that the rate-limiting step is escape from the central pore.